Mesh Generation for Atmospheric Boundary Layer Simulation in Wind Farm Design and Management. (2015) - Gargallo-Peiró, A.; Avila, M.; Owen, H.; Prieto, L.; Folch, A.
Abstract: We propose a new automatic procedure to generate hybrid meshes to simulate turbulent flows for wind farm design and management. In particular, numerical modeling of wind farms involves a RANS simulation of the Atmospheric Boundary Layer (ABL) flow and modeling the turbines using the actuator disc theory. Therefore, the generated meshes have to fulfill several geometrical requirements to answer to the different modeling features. They must: capture the topography features that can influence the wind flow; have a boundary layer close to the terrain to resolve the ABL; be conformally adapted to the disc (turbine) to simulate the turbine effects on the wind flow; be adapted around the disc to capture the wake effect; and present a smooth mesh size transition around the disc to conform the mesh size of the ABL mesh, in which the turbines are immersed. We highlight that the mesh generation procedure is fully automatic once given the mesh size, a topography description, the wind inflow direction, a list of turbine insertion points, and the turbine models. To illustrate the applicability of the proposed procedure, we present two wind farm cases: an offshore wind farm mesh where we illustrate the computed wind deficit, and an onshore farm assimilating real topography data.